Concentração de metais traços na água, sedimento em ascídia Microcosmus exasperatus (Heller, 1878) na baía de Paranaguá, litoral do Paraná - Brasil - Soares, Gésica da Costa Bernardo (2020)
Estuaries are marine environments with high biological productivity that favor human occupation and economic activities, which results in anthropic actions. The water quality of the Paranaguá Estuarine Complex in the marine environment is related to contamination by excess pollutants in the water. Industrial port activities have an impact on marine biota, specifically in estuarine regions where the largest ports in Brazil are located. Some metals (among them, Cr, Cu, Zn, Fe, Cd, Al, Mn) are present in common concentrations, which can significantly affect the quality of life of marine animals. Considering these aspects, the main objective of the work is to evaluate the potential of the ascidians Microcosmus exasperatus as a bioindicator of water contamination by different metallic species and abiotic factors in the Paranaguá Bay. Initially five collection points were chosen, at the points some nutrients were analyzed, such as: nitrite, nitrate, orthophosphate using UV-VIS and metals spectrophotometry methods. Sea squirts were collected, through free diving and manual collection at Ilha da Banana, Prainha do Pasto, Ponta do Ubá and on the Itiberê river (Iate Clube de Paranaque). In the laboratory the acids were brushed, dissected, separating the internal soft body from the tunic and processed to determine the concentration of various chemical elements, including metallic species. In this study some concentrations of nutrients were observed, comparing the water content of the analyzed tissues a significant difference was found between the sites, with higher values in the Itiberê river, indicative of pollution. Metals that are considered highly toxic in high concentrations in water such as Pb> Ni> Cd have lower concentrations than LD, likewise Mn. The other metals Co, Cr, Cu and Fe, were quantified in some collection points, both in the analysis of sediment and in the analysis of the species Microcosmus exasperatus, except for Co which was only found in water. In this way the species is capable of registering high concentrations of trace metals, classifying the environmental quality of the studied region.